The Cambridge companion to creative writing - Morley, David 1964-; Neilsen, Philip 1949- (Cambridge companions to topics, 2012)
"Creative writing has become a highly professionalised academic discipline, with popular courses and prestigious degree programmes worldwide. This book is a must for all students and teachers of creative writing, indeed for anyone who aspires to be a published writer. It engages with a complex art in an accessible manner, addressing concepts important to the rapidly growing field of creative writing, while maintaining a strong craft emphasis, analysing exemplary models of writing and providing related writing exercises. Written by professional writers and teachers of writing, the chapters deal with specific genres or forms - ranging from the novel to new media - or with significant topics that explore the cutting edge state of creative writing internationally (including creative writing and science, contemporary publishing and new workshop approaches)"--Provided by publisher.